1990
DOI: 10.1353/rhe.1990.0026
|View full text |Cite
|
Sign up to set email alerts
|

Critical Thinking Among College and Graduate Students

Abstract: John Dewey (1933) argued that reflective thinking, the careful collection and evaluation of evidence leading to a conclusion, should be a central aim of education. Recent national reports on the quality of post-secondary education in the United States have affirmed the centrality of teaching critical thinking skills to college students (National Institute of Education 1984; Association of American Colleges 1985; Garrison 1984). Yet the empirical evidence documenting progress toward this objective among undergr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
94
1
4

Year Published

1995
1995
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(105 citation statements)
references
References 17 publications
6
94
1
4
Order By: Relevance
“…This finding aligns with the research of Brahmasrene and Whitten (2011), Burbach et al (2012), and Friedel, Irani, and Rhoades et al (2008). However, it is still at odds with the findings of King et al (1990), Bers et al (1996), and Jacobs (1995). Two-thirds of the participants in this study were male, while participants in each of the aforementioned studies were nearly balanced regarding sex.…”
Section: Conclusion and Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This finding aligns with the research of Brahmasrene and Whitten (2011), Burbach et al (2012), and Friedel, Irani, and Rhoades et al (2008). However, it is still at odds with the findings of King et al (1990), Bers et al (1996), and Jacobs (1995). Two-thirds of the participants in this study were male, while participants in each of the aforementioned studies were nearly balanced regarding sex.…”
Section: Conclusion and Discussionsupporting
confidence: 88%
“…However, little consistency surrounds the role of sex in critical thinking development. Some research suggested the rate of critical thinking development among males is higher than females (King, Wood, & Mines, 1990), while other research suggested females possess higher critical thinking abilities (Bers et al, 1996;Rudd et al, 2000). Yet, sex has also been shown to possess limited (Jacobs, 1995) to no significant influence on critical thinking ability (Brahmasrene & Whitten, 2011;Brisdorf-Rhoades, Ricketts, Irani, Lundy, & Telg, 2005;Burbach, Matkin, Quinn, & Searle, 2012;Friedel, Irani, Rhoades et al, 2008;Friedel, Irani, Rudd et al, 2008).…”
mentioning
confidence: 99%
“…Specifically, having higher levels of education is associated with higher levels of availing epistemic beliefs (King et al, 1990). Perhaps this relationship is not surprising given that as one gains more knowledge about a subject it is reasonable to assume that their views of knowledge about that subject also change and become more refined.…”
Section: Teachers' Educational Backgroundmentioning
confidence: 99%
“…Because research has found that obtaining higher levels of education are associated with more availing epistemic beliefs (King, Wood, & Mines, 1990), it seems reasonable to assume that teachers with more advanced mathematical backgrounds would hold more availing epistemic beliefs about mathematics.…”
Section: Teachers' Epistemic Beliefsmentioning
confidence: 99%
“…For instance, the findings reported by Korkmaz (2009) support the findings of the current study. King, Wood & Mines (1990) studied 40 college seniors and 40 graduate students; they found significant main effects for educational level -graduate students scored higher than undergraduates.…”
Section: Edupij • Volume 6 • Issue 2 • 2017mentioning
confidence: 99%